Influence of preoperative urine culture and bacterial species on urogenital sepsis after ureteral flexible lithotripsy in patients with upper urinary tract stones - Wang, Leibo; Yu, Xianzhe; Qiu, Zuze; Liu, Puyu; Tian, Wu; He, Wei; Pan, Yulin; Xu, Feng; Cen, Zhuangding; Ou, Yang; Li, Daobing (Frontiers in Medicine, 2024)
Objective This retrospective study aims to identify risk factors for urogenic sepsis in patients with upper urinary tract stones following ureteral flexible lithotripsy (FURL). Additionally, we analyze the clinical characteristics of bacterial infections post-surgery. Methods A total of 759 patients who underwent FURL at the Urology Department of Zunyi Medical University were included. Univariate and multivariate Logistic regression analyses were conducted to identify independent risk factors for urogenic sepsis post-FURL. The distribution of bacteria based on preoperative urine cultures was also analyzed. Statistical analysis was performed using R4.2.2 software. Results Of the 759 patients, positive preoperative urine culture, urine nitrite positivity, urine white blood cell count (WBC) ≥ 200 cells/μL, residual stones, and neutrophil-to-lymphocyte ratio (NLR) were found to be independent risk factors for urogenic sepsis after FURL. Among the 164 patients with positive preoperative urine cultures, 32 developed urogenic sepsis post-surgery, with 68.75% having positive preoperative cultures. The leading pathogens causing postoperative urogenic sepsis were Escherichia coli (E. coli), Enterococcus faecium, Proteus mirabilis, and Klebsiella pneumoniae. The probabilities of progression to urogenic sepsis were as follows: E. coli 19% (n = 12), Enterococcus faecium 43% (n = 3), Proteus mirabilis 33.3% (n = 1), and Klebsiella pneumoniae 33.3% (n = 1). The ages of affected patients were 47.17 ± 13.2, 53.7, 41, and 79 years, respectively. Rates of comorbid diabetes were 36.4, 66.7, 50, 100%, with nitrite positivity rates at 72.7, 33.3, 50, 0%. Ten female patients were infected with E. coli, while patients infected with Klebsiella pneumoniae had an NLR of 7.62. Conclusion Positive preoperative urine culture, urine nitrite positivity, urine WBC ≥ 200 cells/μL, residual stones, and NLR are independent risk factors for urogenic sepsis after FURL. Escherichia coli is the predominant pathogen post-FURL, with notable female prevalence and nitrite-positive urine in infections. Enterococcus faecium infections are associated with diabetes.